Potret Pluralisme Beragama di Desa Wonoasri Kediri Perspektif Nurcholis Madjid - Huda, M Thoriqul; Nail, Nailul Muna; Rizki, Fatihatur Rizki (Religi: Jurnal Studi Agama-agama, 2024)
Abstact Indonesia is a country rich with various religions, cultures, and tribes, where each community in Indonesia must embrace a religion. Therefore, Indonesia is a pluralistic country in terms of culture, ethnicity, and religion. In Indonesia itself there are not only major religions but also local religions that have been passed down from ancestors for generations. In this study, researchers focused on the interactions that exist in the community in the Portrait of Religious Pluralism from the perspective of Nurcholis Madjid. In conducting this research, the location of the researcher is in Wonoasri Village, Grogol District, Kediri Regency. Where in the village of Wonoasri itself there are Muslims, Christians, and Catholics who have been living side by side and getting along with each other. In this study, researchers focused on the understanding of religious pluralism from the perspective of Nurcholis Madjid in Wonoasri village. In the process of completing this research, researchers used qualitative methods to help the research. The results of this study were found in Wonoasri village, which has a very peaceful, harmonious, and tolerant population, be it Islam, Christianity, and Catholicism in Wonoasri village. These three existing religions coexist and socialize with each other. The people of Wonoasri village have very strong ties, which can work together to foster and instill the values of tolerance and inter-religious pluralism in Wonoasri village. Keywords: Religious Pluralism, Harmony, and Nurcholis Madjid.